Impacts of tropospheric ozone pollution on plant physiology: Current status and future perspectives - Wubiao Li; Yongda Wang; Wenying Jiang (地球与行星物理论评, 2024)
Tropospheric ozone, mainly produced by chemical reactions that involve the photo-chemical oxidation of volatile organic compounds (VOCs) in the presence of nitrogen oxide (NOx), is an air pollutant that adversely impacts human health and natural vegetation. Due to rapid industrialization and urbanization over the last three decades, tropospheric ozone concentrations are rising at a rate of ~0.5%–2% per year. By 2040, ozone concentrations are projected to reach 35–48 ppb (currently ~31 ppb). Thus, the assessment of the effects of this increase on plant physiology is important for ensuring global food security and human health. In this paper, we review the effects of tropospheric ozone pollution on plant physiology, including the visible damage to leaves and roots, changes in photosynthetic rate, carbon sequestration capacity, and the structure of pollen grains. The results show that continuous exposure to high ozone concentrations cause: (1) visible foliar injury, and reduction in the photosynthetic rate and carbon sequestration capacity, which in turn affect the accumulation and distribution of dry matter and consequently reduces crop yields; and (2) damage to cell membranes, protein of pollen grains, and lipid peroxidation in cells, which may increase the risk of respiratory allergies in humans. The response of plants to ozone varies with species, plant growth stage and climatic conditions. Damaged fossil pollen grains have been observed in the sediments of the end-Devonian and the end-Permian, coeval with mass extinction events, which was attributed to increased ozone concentrations resulting from either volcanic eruptions or rapid global warming. These findings highlight the urgent need for research on the impacts of ozone on plant ecological habits in the natural environment, especially on below-ground ecological processes, as well as on measures to mitigate the impacts of ozone on crops and the selection of ozone-resistant crops.